Notes from the school of William de Montibus = Collecta ex diuersis auditis in scola magistri Willelmi de Monte - Samuel, Presbyter ca. um (Toronto medieval Latin texts, 2016)
"Preserved in a single manuscript from the abbey library of Bury St Edmunds, and here edited for the first time, Samuel Presbiter's series of short, extensively annotated poems offers a rare record of one of the innovative formats that medieval schoolmasters used to engage students beyond conventional lectures. The text affords the reader a vivid experience of immersion in the pedagogical techniques of the twelfth-century classroom. The poems and commentary present key lessons from the doctrinal instruction of William de Montibus (c. 1140-1213), the beloved master of the school of Lincoln Cathedral."--